2012
DOI: 10.1155/2012/721817
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Accumulate in the Lung Allergic Inflammation and Efficiently Suppress T-Cell Proliferation but Not Th2 Cytokine Production

Abstract: Foxp3+CD25+CD4+ regulatory T cells are vital for peripheral tolerance and control of tissue inflammation. In this study, we characterized the phenotype and monitored the migration and activity of regulatory T cells present in the airways of allergic or tolerant mice after allergen challenge. To induce lung allergic inflammation, mice were sensitized twice with ovalbumin/aluminum hydroxide gel and challenged twice with intranasal ovalbumin. Tolerance was induced by oral administration of ovalbumin for 5 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 61 publications
(91 reference statements)
3
25
0
7
Order By: Relevance
“…It was previously reported that anti-CD25 treatment could directly abrogate effector CD25 + T cell responses during an inflammatory episode (28). We have shown that both lung CD25 + and CD25 2 T cells are effector cells because they produce substantial amounts type 2 cytokines (14). In this study, we showed that the vast majority of lunginfiltrating CD4 + T cells were CD25 2 , which are not affected by anti-CD25 treatment.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…It was previously reported that anti-CD25 treatment could directly abrogate effector CD25 + T cell responses during an inflammatory episode (28). We have shown that both lung CD25 + and CD25 2 T cells are effector cells because they produce substantial amounts type 2 cytokines (14). In this study, we showed that the vast majority of lunginfiltrating CD4 + T cells were CD25 2 , which are not affected by anti-CD25 treatment.…”
Section: Discussionsupporting
confidence: 51%
“…We have recently shown that Foxp3 + Treg cells accumulate in the lungs of allergic mice and that the majority of these cells upregulated CCR4, CD69, and CD54 and drastically downregulated CD62L, a phenotype that resemble effector/memory T cells, distinguishing from naive CCR4 low CD69 2 CD54 low CD62L high Treg cells (14). Our in vitro studies showed that highly purified infiltrating lung Treg cells efficiently suppress pulmonary Th cell proliferation but fail to inhibit type 2 cytokine production (14).…”
mentioning
confidence: 79%
See 3 more Smart Citations